Experimental study on shear mechanical properties of improved loess based on rubber particle incorporation and EICP technology - Chen, Yong; Chai, Shaoqiang; Cai, Dongbo; Wang, Wei; Li, Xianpeng; Liu, Jinhao (Frontiers in Earth Science, 2023)
Loess is often not suitable for direct use as a roadbed or building foundation due to its collapsibility, and it needs to be improved by adding curing agents. Taking the loess in Xi'an area as the research object, the reinforcement of loess was carried out using waste tire rubber particles and Enzyme Induced Carbonate Precipitation (EICP) technology. The change of shear strength and shear strength index of improved soil with rubber content and rubber particle size under different strengthening conditions was analyzed, and the strengthening mechanism was also expounded. The results show that rubber powder can improve the shear strength of loess to a certain extent, and the combination of EICP technology can increase the strength of improved loess by nearly 50%. In addition, rubber particles have a certain inhibitory effect on EICP, and the shear strength growth rate decreases with the increase of rubber content. When the rubber particle size is 1-2mm, the shear strength growth rate is the highest. It is suggested that when adding rubber particles or adding rubber particles combined with EICP technology is used to improve loess, the rubber particle size should be selected as 1-2mm, and the content is about 10%. The test results can provide a scientific basis for the reduction of geologic disasters in loess areas, and at the same time can provide a non-polluting way for the disposal of waste tires.